Risk and protective factors surrounding depressive symptoms and hazardous alcohol use among intimate partner violence survivors in Nairobi, Kenya - Balaji, Suvasini (Journal of family violence, 2025)
Purpose: In informal settlements of Nairobi, Kenya, intimate partner violence (IPV) has higher prevalence than national and global averages, and is associated with increased risk of depression and alcohol use. This study examined correlates of depressive symptoms and hazardous alcohol use among IPV survivors in Nairobi’s informal settlements. Method: This cross-sectional secondary analysis of baseline data from a 2018 randomized controlled trial examined depressive symptoms and hazardous alcohol use among 352 IPV survivors in Nairobi’s informal settlements. Logistic regressions examined associations between individual-level, partner-level, psychosocial (abuse recognition, self-blame), protective factors (self-efficacy and resilience), and depressive symptoms and hazardous alcohol use. Results: Most participants (95%) met criteria for depression (CESD > = 10 threshold), and 17% exhibited hazardous alcohol use. Resilience was high (Median: 18.0; Range: 0-40), as was self-efficacy (Median: 19.0; Range: 6-24). Depressive symptoms, dichotomized at the median ( > = 22) for regression analysis, were associated with recognition of abuse (aOR: 2.35; p < 0.001) and self-blame (aOR: 1.61; p < 0.05). Hazardous alcohol use was associated with partnership characteristics, specifically concurrent partners (aOR: 4.25; p < 0.01) and partnership length (longer was protective; aOR: 0.88; p < 0.05); ethnic differences were also identified. Resilience functioned as a risk factor for both depression (aOR: 2.98, p < 0.01) and hazardous alcohol use (aOR: 2.79, p < 0.05), rather than a protective factor. Conclusions: Self-blame contributed to depressive symptoms among women experiencing IPV, even when accounting for resilience. Addressing IPV-related self-blame is an actionable strategy that may help mitigate depression. Expanding access to IPV-related supports is an actionable step in improving the mental health of survivors.